Prelude to medical tourism : Singapore as the host destination. - Hu, Fang. (2013)
This paper focuses on the supply perspective of Singapore as medical tourism host destination since the supply of medical tourism forms the bedrock of the overall industry. To have a distinct understanding on the supply perspective of medical tourism in Singapore, an integrated theoretical framework is adopted. The framework is able to review the initiatives put in by the public and private sectors in promoting medical tourism industry by a neutral perspective. The current infrastructure, facilities, promotional activities, quality assurance and communication structures in Singapore will be emphasized in the report. A qualitative research method was adopted and data from secondary resources such as Singapore’s Ministry of Health (MOH), Statistics Singapore (Singstat), and academic literature were reviewed. The results have shown concrete evidence of excellence achievements by Singapore in medical tourism. For instance, private investment on infrastructure has fulfilled the insatiable demand of medical tourists and promotion efforts by public and private sectors have been done aggressively. The implications are also discussed to give insights on how Singapore can better perform in the future to establish an outstanding medical tourism hub.